Microfluidic devices for cell separation and sample concentration - Ning, Liu (2018)
Microfluidic platforms for cell separation and downstream bio-sample analysis provide powerful tools for biomedical fundamental research and practical applications. Therefore, the overall goal of my dissertation is to develop such integrative platforms using novel techniques. We first develop a magnetofluidic device using microelectromagnets for magnetic field generation and applied it for cancer cell separation. The cell separation efficiency can reach up to 79 % using 1A electric current. This tunable device would be a promising platform to separate many types of cells. Next, we propose a hybrid size and affinity-based multiplexed cell sorter, consisting spiral channel, inertial alignment segment and magnetic separation part. This is the first platform integrating spiral inertial microfluidics and magnetophoretic separation technique in one single chip. Using blood cell sample, a good separation performance (>90% efficiency) is achieved. This novel hybrid platform offers a promising alternative to many existing cell separation technologies. Sample concentration technology is another critical aspect of biomedical innovation. Utilizing our developed fabrication techniques, we establish paper-based microfluidic platforms using ion concentration polarization effect for bio-sample concentration. The sample concentration performances are comparable with other reported results. Our paper-based platforms and fabrication techniques hold great promise for creating simple and inexpensive paper-based assays, which can be used for practical point-of-care (POC) diagnostics.